Third Party Legal Remedies Against the Decision to Confiscate Goods Not Belonging to the Defendant in A Corruption Case (Case Study of Determination Number. 01/objection/Pid.Sus-TPK/2022/PN.Plg Jo. Number. 16/Pid.Sus-TPK/2022/PN.Plg) - Defriansyah*, Andrie; Yusuf, Hambali; Salia, Erli; Mahfuz, Abdul Latif (Riwayat: Educational Journal of History and Humanities, 2023)
This paper examines the legal remedies that can be taken by third parties against the decision to seize goods that do not belong to the defendant in corruption cases. The focus is on objections to asset forfeiture decisions by the Palembang District Court. The method used is Normative Legal Research with a Descriptive-Analytical approach, utilizing Primary, Secondary, and Tertiary Legal Materials. Analysis is done qualitatively with deductive inference. The results show that a Good Faith Third Party can file a written objection to goods seized by the state. The owner or guardian of the goods must file an objection within two months after the verdict is pronounced. The Judge's consideration in giving the verdict is based on Supreme Court Regulation Number 2 of 2022, which regulates the procedure for resolving objections from third parties in cases of seizure of corruption assets. This research provides insight into the mechanism for protecting third party rights in the process of recovering state assets.